TINGKAT KEJADIAN PARASIT Anisakis sp. PADA IKAN CAKALANG (Katsuwonus pelamis) DAN IKAN TONGKOL (Auxis thazard) YANG DIJUAL DI TEMPAT PENJUALAN IKAN PASIR PANJANG KOTA KUPANG - Odulfus Salmon Hibur; Annytha Ina Rohi Detha; Julianty Almet; Irmasuryani . (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Fish as a source of nutrients for the content of high value and high protein, omega 3, minerals and vitamins A and D for humans as well as human resources for the economy. Various species of tuna can be found in almost all waters of NTT, as a migration destination of the various species of tuna. Various species of marine fish known as intermediate host of different species of parasites, including nematodes Anisakis Anisakiasis which is the causative agent in humans. Anisakiasis can occur in humans after consumption of raw or undercooked fish infected by Anisakis sp, particularly in East Nusa Tenggara, the information about the fish Anisakis infection has not been reported and not well documented. Because it was in doing this research, conducted by collecting larvae of nematodes of the two species of tuna (Katsuwonus pelamis) tuna (Auxis thazard) from the sale of fish Pasir Panjang Kota Kupang. Organs are examined, namely the abdominal cavity, internal organs and muscle tissue. The larvae of nematodes be identified morphologically showed Anisakis sp, then separated for the calculation of Anisakis larvae. Parasites in fiksasi in 70% alcohol, followed by coloring Carmine, and the calculation of Anisakis larvae. The morphology, Anisakis sp. can be distinguished by other parasites by their ventriculus and mukron are clearly visible on Anisakis sp. under a stereo microscope. Anisakis sp . Found from the swordfish and fish skipjack all of them including Anisakis type i characterized by the presence of boring tooth on the tip of the anterior and mukron the percentage. Where as prevalence of the parasite Anisakis sp. on skipjack (Katsuwonus pelamis) that of 50 samples that were observed, as many as 8 samples were infected with Anisakis sp. with a prevalence of 16% value. While the tuna (Auxis thazard) of the 50 samples was observed, which infected 10 samples with grades prevalence of 20%.